Jasper John Dooley, you're in trouble - Adderson, Caroline, 1963- (Adderson, Caroline, 1963- Jasper John Dooley, 2015)
When Jasper John Dooley buys a can of Torpedo High Energy Drink accidentally, he knows he shouldn't drink it. His parents had warned him about "bad" drinks that are full of things like sugar and caffeine. But Jasper finds the drink irresistible. Before Jasper knows what hit him, the caffeine and sugar in the energy drink fuels all kinds of misbehavior. Is there anything that can bring him back to his senses?